Genealogi Temuan Naskah-Naskah Kuno Keislaman di Gunung Kawi Malang - Awalin, Fatkur Rohman Nur (Arnawa, 2024)
Mount Kawi in Malang continues to be recognized as a site imbued with an enduring sense of enchantment. Interestingly, ancient manuscripts linked to Islamic teachings have also been discovered in this region, particularly as part of the private collection of Mr. Anut Ekowiyono. These manuscripts, predominantly inscribed in Pegon Arabic script, serve as a focal point for this study, which investigates their genealogy and historical significance. The manuscripts, according to Mr. Anut Ekowiyono, were inherited from his great-grandfather, who hailed from Bangil (Pasuruan), Ponorogo, and Gunung Kawi itself. This lineage highlights the connection between the manuscripts and the broader historical and cultural networks of Java. The presence of these manuscripts at Gunung Kawi provides valuable evidence of the Islamisation process led by Javanese scholars in this region, suggesting that Gunung Kawi served as an important site for religious and cultural transformation. Culturally, Gunung Kawi has long been significant, functioning as a boundary and a point of cultural continuity. During the ancient Javanese period, it marked the division between the land of Kāḍiri and Tumapel in the 12th century—a time dominated by Hindu-Buddhist kingdoms such as Singosari and Majapahit. In the Islamic colonial era, the site maintained its cultural significance, delineating the boundary between Islamic Mataram and Arek culture. This layered history underscores Gunung Kawi’s role as a dynamic cultural and religious frontier throughout Javanese history. === Gunung Kawi di Malang hingga saat ini masih dikenal dengan citranya sebagai tempat pesugihan. Namun, di sisi lain ditemukan pula naskah-naskah kuno yang berkorelasi dengan ajaran Islam. Temuan naskah-naskah kuno di Gunung Kawi Malang merupakan koleksi pribadi Bapak Anut Ekowiyono. Mayoritas naskah-naskah kuno ditulis menggunakan aksara Arab pegon. Kajian ini mengkaji genealogi temuan naskah-naskah kuno di Gunung Kawi Malang yang dimiliki pribadi oleh Bapak Anut Ekowiyono. Hasilnya naskah-naskah kuno di Gunung Kawi Malang yang dimiliki pribadi oleh Bapak Anut Ekowiyono merupakan warisan turun temuran dari kakek buyutnya. Berdasarkan wawancara dengan Bapak Anut Ekowiyono kakek buyutnya berasal dari Bangil (Pasuruan), Ponorogo dan dari Gunung Kawi Malang sendiri. Keberadaan naskah-naskah kuno di Gunung Kawi Malang bukti sahih bahwa terdapat proses Islamisasi oleh ulama Jawa di Gunung Kawi Malang. Secara kebudayaan pada masa Jawa kuno Gunung Kawi Malang batas kultural dan sebagai kontinuitas budaya antara bumi Kadhiri (kāḍiri) dan bumi Tumapel pada abad ke 12 (masa Hindu-Buddha) terutama Singosari sampai Majapahit. Pada jaman Islam-kolonial menjadi batas kultural antara Mataram Islam dan kebudayaan Arek.